Pengaruh Gadget Terhadap Minat Belajar Siswa SMK Muhammadiyah 5 Kepanjen Dengan Metode TAM - Wahyu Candra Setyaji; Novia Ratnasari; Anisa Hudi Widaningrum; Farid Wahyudi; Zurriat Nyndia Rahmawati (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Technology is developing at a rapid pace, and this significantly affects our daily lives. Gadgets have transformed our lifestyle, particularly in the field of education. One of the aspects impacted is students' learning interest. Students tend to focus more on subjects they are interested in, and less on those they are not. Learning interest is influenced by both internal and external factors, with gadget use being one of the external factors. The purpose of this study is to determine the extent to which gadgets influence students' learning interest at SMK Muhammadiyah 5 Kepanjen, Malang Regency. The data used in this research is primary data collected through questionnaires. The population consists of 275 students, with a sample of 163 tenth-grade students from all vocational programs at SMK Muhammadiyah 5 Kepanjen. The findings indicate that gadgets have a significant influence on students' learning interest, as evidenced by a significance value (sig.) lower than the probability value (0.001 < 0.05) and a t-calculated value greater than the t-table value (10.745 > 1.975).